Therapeutic management of arthritis: A review on structural and target‐based approaches. Issue 11 (18th July 2022) - Mahore, Anjali; Kamboj, Payal; Kaleem, Mohammad; Amir, Mohammad
Abstract: Inflammation is the natural defense mechanism against any external stimuli in the human body and it saves us from foreign entities that may alter our bodies' normal functioning. Any anomaly in this natural defense system leads to the development of different pathological conditions associated with chronic inflammation like rheumatoid arthritis, osteoarthritis, atopy, asthma, allergic rhino‐conjunctivitis, coronary artery disease, cardiac arrhythmias, obesity, insulin resistance and type‐2 diabetes, depression, and aging. These disorders impair the quality of life of affected people in different ways. Among these, rheumatoid arthritis and osteoarthritis are the most common chronic inflammation‐associated disorders. Different therapeutic strategies are already available for the treatment of rheumatoid arthritis and osteoarthritis, but all with pros and cons. Here, we discuss the emergence of several antiarthritic analogs developed by different researchers which could provide the basis for the evolution of newer therapeutic strategies with better activity and safety profiles. Abstract : Different therapeutic strategies are already available for the treatment of rheumatoid arthritis and osteoarthritis, but all with advantages and disadvantages. This review discusses the development of new drug candidates acting through different mechanisms of action, which could provide the basis for the evolution of newer therapeutic strategies with better activity and safety profiles.